Dissociative recombination and vibrational excitation of BF+ in low energy electron collisions. (12th September 2016) - Zs Mezei, J; Colboc, F; Pop, N; Ilie, S; Chakrabarti, K; Niyonzima, S; Lepers, M; Bultel, A; Dulieu, O; Motapon, O; Tennyson, J; Hassouni, K; et al.
Abstract: The latest molecular data—potential energy curves and Rydberg-valence interactions—characterising the super-excited electronic states of BF are reviewed in order to provide the input for the study of their fragmentation dynamics. Starting from this input, the main paths and mechanisms of BF +  dissociative recombination and vibrational excitation are analysed. Their cross sections are computed for the first time using a method based on the multichannel quantum defect theory (MQDT), and Maxwellian rate-coefficients are calculated and displayed in ready-to-be-used format for low temperature plasma kinetics simulations.